2016
DOI: 10.2460/ajvr.77.11.1227
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of brain perfusion in healthy dogs by means of magnetic resonance imaging

Abstract: OBJECTIVE To determine values of perfusion parameters determined via MRI in the brains of healthy dogs. ANIMALS 10 healthy adult Beagles. PROCEDURES Each dog was anesthetized for MRI examination of the brain, including standard sequences and a perfusion-weighted sequence. Gadoteric acid (0.2 mmol/kg) was injected IV at a rate of 5 mL/s. A dedicated workstation was used to measure the times from contrast medium injection to arrival at an ROI (TO) and peak contrast enhancement (TTP), mean contrast medium transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…However, a PET and perfusion-based MR techniques of CBF measurements were found to be highly consistent in studies involving both humans ( 24 , 37 , 38 ) and dogs ( 39 , 40 ). The values extracted from our study of clinically normal CKCSs come close to those measured in studies using MRI- or CT-based perfusion studies ( 39 , 40 ), but differ from others ( 17 , 22 ). However, several factors limit the comparison of the present investigation with other studies.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, a PET and perfusion-based MR techniques of CBF measurements were found to be highly consistent in studies involving both humans ( 24 , 37 , 38 ) and dogs ( 39 , 40 ). The values extracted from our study of clinically normal CKCSs come close to those measured in studies using MRI- or CT-based perfusion studies ( 39 , 40 ), but differ from others ( 17 , 22 ). However, several factors limit the comparison of the present investigation with other studies.…”
Section: Discussionsupporting
confidence: 75%
“…MR-perfusion techniques have proven to be feasible in dogs ( 22 , 23 ) but accuracy and validity of the method for its standard use must be further evaluated. Positron emission tomography (PET) is considered to be the gold standard for studying cerebral hemodynamics ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia can alter CBF and, therefore, possibly influence lactate concentrations. In a previous study, 27 CBF in dogs with idiopathic epilepsy was compared with a similar research project 28 in healthy dogs. It was found that anesthetics should only minimally affect lactate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…TTP was defined as the time difference in peak intensity and the BAT [85,94]; 2.) TTP was defined as the time from bolus injection to peak intensity [53,54,76,95]; and 3.) TTP maps were generated using a normalization by subtracting a mean contralateral ROI of the unaffected hemisphere [54,[71][72][73]75].…”
Section: Discussionmentioning
confidence: 99%